A Compact and Fast Resonant Cavity-Based Encoder in Photonic Crystal Platform - Mohammad Soroosh; Faris K. AL-Shammri; Mohammad Javad Maleki; Venkatachalam Rajarajan Balaji; Ehsan Adibnia (Crystals)
A novel 4-to-2 photonic crystal encoder is proposed by modulating the intensity of four input optical signals, and four distinct output states are achieved. Nonlinear rods are employed to couple input waves into resonant cavities, directing the light to the desired output waveguides. The proposed design, with a footprint of 114 µm2, demonstrates efficient encoding operation at a wavelength of 1550 nm and is highly suitable for integrated photonics applications. A comprehensive comparative analysis revealed that the proposed 4-to-2 encoder exhibits a time response 176 fs faster than previously presented encoders. Furthermore, the contrast ratio of the designed structure is as high as 13.78 dB to distinguish between logic 0 and 1. These advancements hold significant potential for enhancing the performance of compact, high-speed digital circuits.